Ecological Tauhid-Based Green School Management: A Case Study of Eco-Pesantren Implementation at Mambaul Ulum Islamic Junior High School, Pamekasan - Muin, Abdul; Rosyid, Moh. Zaiful; Rahman, Habibur; Rofiqi, Rofiqi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
The escalating global environmental crisis demands active participation from educational institutions, particularly Islamic institutions with unique theological foundations for environmental stewardship. This research addresses the gap between Islamic values and modern environmental management by analyzing the innovative “Eco-Pesantren Model” at SMPI Mambaul Ulum, identifying implementation mechanisms, and evaluating impacts on students’ environmental awareness. Using qualitative case study methodology with participatory observation, in-depth interviews with 25 key informants, and document analysis, this research develops an integrated model combining spiritual transformation with practical environmental management. The study introduces “Ecological Tauhid” concept, integrating modern environmental principles with Islamic values through Contextual Environmental Fiqh. Implementation includes four programs: Zero Waste Islami (85% consistent waste sorting), Blessed Energy (40% electricity reduction), Water of Life (ablution water reduction from 12 to 3 liters), and Islamic value-based environmental curriculum (environmental fiqh understanding increased from 72 to 86 points). The “Environmentally Conscious Family” program achieved 78% family participation with 60% plastic waste reduction. This research contributes the “Ecological Tauhid” paradigm as a new framework for Islamic environmental education, providing a replicable model supporting SDGs 4, 13, and 15.